2019
DOI: 10.1093/pm/pnz317
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Dose and Benzodiazepine Use Among Commercially Insured Individuals on Chronic Opioid Therapy

Abstract: Objective To examine morphine milligram equivalent (MME) trends, use of concurrent opioids and benzodiazepines, and opioid-related emergency department (ED) visits or hospitalizations in a national cohort of patients on chronic opioid therapy. Design Retrospective cohort analysis of prospectively collected data from the Truven Health MarketScan Commercial Claims and Encounters database from 2009 to 2015. This includes individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Given that there is no international standard for measuring the level of hospital opioid consumption, comparisons were made between our collected data and existing foreign published studies on drug utilization and opioid consumption evaluations in hospital settings based on the ATC/DDD system. We confirmed the hypothesis of our study, that is, opioid consumption at this hospital was relatively low compared with the consumption rates reported in other studies, which included two hospitals and four databases from Europe, East Asia, and North America (12)(13)(14)(15)(16)(17). One study using the same measurement unit (DDD/100 bed-days), carried out in a hospital in Madrid, Spain, revealed that opioid consumption had a remarkable increasing tendency, from 22.3 DDD/100 bed-days in 2011 to 26.5 DDD/100 beddays in 2015 (16).…”
Section: Discussionsupporting
confidence: 91%
“…Given that there is no international standard for measuring the level of hospital opioid consumption, comparisons were made between our collected data and existing foreign published studies on drug utilization and opioid consumption evaluations in hospital settings based on the ATC/DDD system. We confirmed the hypothesis of our study, that is, opioid consumption at this hospital was relatively low compared with the consumption rates reported in other studies, which included two hospitals and four databases from Europe, East Asia, and North America (12)(13)(14)(15)(16)(17). One study using the same measurement unit (DDD/100 bed-days), carried out in a hospital in Madrid, Spain, revealed that opioid consumption had a remarkable increasing tendency, from 22.3 DDD/100 bed-days in 2011 to 26.5 DDD/100 beddays in 2015 (16).…”
Section: Discussionsupporting
confidence: 91%